Annual Plan and Budget-Link 1968-69 Government of Assam - Planning Commission (Planning Commission, 1968)
Summary statement of State Plan outlays and budget provisions for 1968-69 by heads of development Scheme-wise Plan outlay and Budget Provisions, Schemewise analysis in terms of Plan and Budget List of Centrally Sponsored Schemes to be implemented during 1968-69, List of Centrally Sponsored Schemes indicating outlays plan and budget provisions in full
Government of Assam Planning and Development Department